2012
DOI: 10.1017/thg.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

The Healthy Twin Study, Korea Updates: Resources for Omics and Genome Epidemiology Studies

Abstract: The Healthy Twin Study, Korea (HT) is an ongoing multi-center cohort study that was initiated in 2005, based on a nation-wide twin and family database. Since its inception, the HT has recruited 815 pairs of adult twins and a total of 3,690 individual twins and their families as of July 2012. Here we summarize updates since the previous report in 2006. Besides the increase in size, the HT has been enriched in several aspects: a biobank was constructed for ongoing and future omics studies; and genome-wide single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 9 publications
3
26
0
Order By: Relevance
“…Baseline characteristics of the 8,074 Koreans from the Healthy Twin 1517 and KARE3 18 studies are shown in Supplementary Table 2e. In this sample, only HapMap imputed (HapMap3 Phase 2 and Korean HapMap) data were available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of the 8,074 Koreans from the Healthy Twin 1517 and KARE3 18 studies are shown in Supplementary Table 2e. In this sample, only HapMap imputed (HapMap3 Phase 2 and Korean HapMap) data were available.…”
Section: Resultsmentioning
confidence: 99%
“…In each of six new loci, we confirmed expression levels of genes nearest the novel variants in lung tissue and performed expression quantitative trait locus (eQTL)-analyses in 762 whole blood samples. We evaluated the new loci in 6,070 African Americans in the National Heart, Lung and Blood Institute (NHLBI)-sponsored Candidate gene Association Resource (CARe) Project, in a Chinese subset (n=563) of the Multi-Ethnic Study of Atherosclerosis (MESA), in a Hispanic subset (n = 849) of MESA, and in Koreans (n = 8,074) from two cohort studies; Healthy Twin 1517 and Korea Association Resource 3 (KARE3) 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Two population cohorts of Koreans with genome-wide genetic marker information were involved in this study; the Korea Association Resource study (KARE), consisting of 8,842 individuals, and the Healthy Twin study (HT) with 3,079 individuals ( 19,20 ). The KARE served as discovery data for associated loci and validation was performed using the HT data.…”
Section: Subjectsmentioning
confidence: 99%
“…Most protocols are shared between the KARE and the HT, and more detailed protocols are available in previous literature ( 20 ). A total of 3,079 study participants (n = 1,217 men, n = 1,862 women, from 17-81 years of age) were enrolled since 2005; 531 monozygotic twin pairs, 120 dizygotic twin pairs, and 1,777 non-twin family members in 661 families.…”
Section: Subjectsmentioning
confidence: 99%
“…The Healthy Twin Study, a nationwide, twin-family cohort study in Korea, recruited Korean adult twins and their family members who had no ascertained preexisting syndromic diseases. 11,15 The study population comprised 282 families with different types of relationships: 360 MZ (180 pairs), 87 DZ (42 pairs of twins and one pair of triplets), 304 nontwin siblings, and 278 spouses (139 pairs). A zygosity questionnaire and discriminating algorithms were used to determine MZ and DZ.…”
Section: Study Populationmentioning
confidence: 99%